CRITERIA FOR DETERMINING THE GENRE OF HISTORICAL DRAMATIC WORKS AND THE DRAMA JALOLIDDIN MANGUBERDI - Mamatvaliev Mukhammad Kuymurodovich (International Journal of Literature and Language Studies, 2026)
ABSTRACT. This article provides a scientific and theoretical analysis of the role of the principle of sociality in defining the genre of a work of art on a historical theme. Specifically, the criteria for determining genres within the dramatic form are re-examined using the example of Makhsud Shaykhzoda's work "Jaloliddin Manguberdi." The study argues that the work belongs to the genre of drama, not tragedy, based on the character of its social reality, the nature of its conflict, and the relationship between historical truth and artistic invention. Additionally, existing views in literary criticism are critically analyzed, and it is substantiated that the protagonist's fate and social turning points are decisive factors in defining the genre.